(untitled) (Multidisciplinary Journal of Science and Technology, 2026)
Central nervous system tumors (CNS tumors) are heterogeneous neoplasms arising from the brain and spinal cord tissues, characterized by complex diagnostic, therapeutic, and prognostic features. The aim of this article is to identify the epidemiology, pathogenesis mechanisms, classification, diagnostic methods, and modern treatment strategies of CNS tumors, as well as to analyze factors affecting patient outcomes. The study was conducted based on a literature review, highlighting the most recent clinical and molecular research. The results show that molecular genetic biomarkers and advanced imaging techniques increase diagnostic accuracy in identifying and subtyping CNS tumors. Furthermore, combined strategies of surgery, radiotherapy, and targeted pharmacotherapy are effective in prolonging overall survival and improving symptom control. In conclusion, an integrated approach to CNS tumors is crucial for optimizing individualized treatment plans and improving clinical outcomes.